PENGARUH SELF-EFFICACY DAN MOTIVASI BELAJAR TERHADAP KEMANDIRIAN BELAJAR MATEMATIKA - Nurul Laili (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2021)
The study aims to investigate: 1) The effect of self-efficacy on the independene learning of mathematics; 2) The effect of learning motivation on the independene learning of mathematics; 3) The effect of self-efficacy and learning motivation as an aggregate on the independene learning of mathematics. This type of research is a quantitative with an approach ex-post facto. The population in this research is eight grade students of SMP Negeri 1 Musuk. Sampling was done by using purposive sampling is class VIII G SMP Negeri 1 Musuk. The data were collected through a questionnaire and documentation. The hypothesis testing used simple regression analysis and multiple regression analysis. The results of the study are as follows. 1) There is a positive effect and significant of self-efficacy on the independene learning of mathematics, indicated by a correlation coefficient value of 0.770, a determination coefficient value 0,593 and tvalue ttable of (6,6062,042); 2) There is a positive effect and significant of learning motivation on the independene learning of mathematics, indicated by a correlation coefficient value of 0,852, a determination coefficient value 0,727 and tvalue ttable of (8,9282,042); 3) There is a positive effect and significant of self-efficacy and learning motivation on the independene learning of mathematics, indicated by a correlation coefficient value of 0,873, a determination coefficient value 0,762 and Fvalue Ftable of (8,9282,042).